Functions of the Membrane-Associated and Cytoplasmic Malate Dehydrogenases in the Citric Acid Cycle of Corynebacterium glutamicum - Molenaar, Douwe (American Society for Microbiology, 2000)
Like many other bacteria, Corynebacterium glutamicum possesses two types of l-malate dehydrogenase, a membrane-associated malate:quinone oxidoreductase (MQO; EC 1.1.99.16) and a cytoplasmic malate dehydrogenase (MDH; EC 1.1.1.37) The regulation of MDH and of the three membrane-associated dehydrogenases MQO, succinate dehydrogenase (SDH), and NADH dehydrogenase was investigated. MQO, MDH, and SDH activities are regulated coordinately in response to the carbon and energy source for growth. Compared to growth on glucose, these activities are increased during growth on lactate, pyruvate, or acetate, substrates which require high citric acid cycle activity to sustain growth. The simultaneous presence of high activities of both malate dehydrogenases is puzzling. MQO is the most important malate dehydrogenase in the physiology of C. glutamicum. A mutant with a site-directed deletion in the mqo gene does not grow on minimal medium. Growth can be partially restored in this mutant by addition of the vitamin nicotinamide. In contrast, a double mutant lacking MQO and MDH does not grow even in the presence of nicotinamide. Apparently, MDH is able to take over the function of MQO in an mqo mutant, but this requires the presence of nicotinamide in the growth medium. It is shown that addition of nicotinamide leads to a higher intracellular pyridine nucleotide concentration, which probably enables MDH to catalyze malate oxidation. Purified MDH from C. glutamicum catalyzes oxaloacetate reduction much more readily than malate oxidation at physiological pH. In a reconstituted system with isolated membranes and purified MDH, MQO and MDH catalyze the cyclic conversion of malate and oxaloacetate, leading to a net oxidation of NADH. Evidence is presented that this cyclic reaction also takes place in vivo. As yet, no phenotype of an mdh deletion alone was observed, which leaves a physiological function for MDH in C. glutamicum obscure.